2023
DOI: 10.34172/jlms.2023.19
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Photobiomodulation Therapy With an 810-nm Diode Laser on Pain Perception Associated With Dental Injections in Children: A Double-Blind Randomized Controlled Clinical Trial

Bahman Seraj,
Anise Bavaghar,
Neda Hakimiha
et al.

Abstract: Introduction: This study investigated the photobiomodulation effect of an 810-nm diode laser in adjunction with topical anesthesia on pain perception during infiltration anesthesia of primary maxillary molars in children. Methods: This double-blind randomized controlled clinical trial was conducted on 64 children (aged 5-9 years) requiring extraction or stainless steel crown for their primary maxillary molars. The patients were randomly allocated into two groups (n=32) of laser and control. In the laser group,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…Khan et al did not report the type of anesthesia used [ 24 ]. The injection was performed by different providers, clinicians injected the local anesthetic in two studies [ 30 31 ], pediatric dentists in three study [ 27 28 29 ], a blinded investigator in two studies [ 32 33 ], a principal investigator in one study [ 25 ], an oral and maxillofacial surgeon (OMFS) in one study [ 26 ], a senior post-graduate student of pediatric dentistry in one study [ 34 ], a general dentist in one study [ 35 ] and two RCTs did not indicate who performed the injections [ 22 24 ]. Eleven RCTs indicated the use of a 27-gauge needle, while two studies did not disclose the needle size [ 24 25 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Khan et al did not report the type of anesthesia used [ 24 ]. The injection was performed by different providers, clinicians injected the local anesthetic in two studies [ 30 31 ], pediatric dentists in three study [ 27 28 29 ], a blinded investigator in two studies [ 32 33 ], a principal investigator in one study [ 25 ], an oral and maxillofacial surgeon (OMFS) in one study [ 26 ], a senior post-graduate student of pediatric dentistry in one study [ 34 ], a general dentist in one study [ 35 ] and two RCTs did not indicate who performed the injections [ 22 24 ]. Eleven RCTs indicated the use of a 27-gauge needle, while two studies did not disclose the needle size [ 24 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…Eleven RCTs indicated the use of a 27-gauge needle, while two studies did not disclose the needle size [ 24 25 ]. The injection technique used was mostly buccal infiltration [ 22 25 30 31 34 ]; two studies reported using both buccal and palatal injection [ 26 34 ], one reported using palatal injection only [ 35 ] and one did indicate the injection technique [ 24 ]. All studies used only one injection; however, three did not report the number of injection used [ 24 25 32 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations